The Many Forms of "Good Ageing": Noticing Alignments and Frictions in Digital Innovation Initiatives / Las múltiples formas del “buen envejecimiento”: Alineaciones y fricciones en proyectos de innovación digital para personas mayores / Le molte forme di “buon invecchiamento”: Notare allineamenti e attriti nelle iniziative di innovazione digitale - Greubel, Carla; Stalenhoef, Hanna; van Hees, Susan; Moors, Ellen H. M.; López Gómez, Daniel; Peine, Alexander (KULA)

(untitled) (University of Victoria Libraries, 2025)
Digital health and social care innovations for older people embody specific ideas about “good ageing.” But what does good ageing mean to older adults themselves? And how do their ideas and practices relate to the ideas of good ageing that have informed the design of those digital tools that they are invited to engage with? Our research comic explores these questions by drawing on eight months of ethnographic fieldwork in three innovation initiatives that trial and implement health and social care innovations for older people in Italy, Spain, and the United Kingdom.Presenting our research in the format of a research comic is an explicit attempt at sharing everyday experiences of ageing and technology with a broader audience including researchers but also older adults, city and community councils, social workers, and technology developers with whom we collaborated in the field. The drawings, fieldwork quotes, and accompanying reflections illustrate the diverse and sometimes conflicting forms of good ageing that shape users’ engagement with proposed technologies. As such, the research comic invites the reader to question dominant perceptions of technologies as simple tools that facilitate good ageing. It highlights the importance and value of geographical, cultural, and affective closeness to the everyday lives of those for and with whom these technologies are designed. Such closeness, we argue, is a first step in being able to notice conflicts between different forms of good ageing and to adjust digital tools and services in such a way that they facilitate forms of good ageing that older adults themselves find relevant.